Effects of non-invasive brain stimulation on emotion regulation in patients with attention deficit hyperactivity disorder: a systematic review - Shen, Fang; Zhou, Hui (Frontiers in Psychiatry, 2024)
Background and objectiveA growing body of research evidence suggests that many patients with attention deficit hyperactivity disorder (ADHD) have difficulties with emotion regulation. Non-invasive brain stimulation (NIBS), which mainly includes transcranial electrical stimulation (tES) and repetitive transcranial magnetic stimulation (rTMS), has been considered a potential new direction in the treatment of emotion dysregulation in ADHD patients. The key components of tES are transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS). However, there is no systematic evaluation exploring the effects of non-invasive brain stimulation on emotion regulation in ADHD patients. Therefore, this systematic review aimed to summarize the effects of NIBS on emotion regulation in ADHD patients.MethodsThis systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched PubMed, Embase, Web of Science, and the Cochrane Library electronic databases up to 1 July 2024. We also hand-searched the reference lists of retrieved articles and reviews. Assessing risk of bias using the Cochrane Assessment Tool.ResultsThrough database search, we obtained a total of 1134 studies, of which 5 met the inclusion criteria. Statistically significant improvements in emotion regulation in children with ADHD were observed in 1 study after treatment with tDCS. In the remaining 4 studies (2 with tDCS and 2 with rTMS), there were no statistically significant changes in emotion regulation in ADHD patients after treatment with either tDCS or rTMS.ConclusionsThe data from our preliminary study do not allow us to draw definitive conclusions that non-invasive brain stimulation improves emotion regulation in ADHD patients. This is because there is a paucity of literature on the effects of tES or rTMS on emotion regulation in ADHD patients and a limited number of randomized controlled trials. More high-quality multicenter randomized controlled trials exploring the efficacy of non-invasive brain stimulation on emotion regulation in ADHD patients are needed in the future to provide strong evidence for definitive conclusions before it can be considered as a potential treatment option.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024569041.